The transcription of the alarmin cytokine interleukin-1 alpha is controlled by hypoxia inducible factors 1 and 2 alpha in hypoxic cells - Rider, Peleg; Kaplanov, Irena; Romzova, Marianna; Bernardis, Liora; Braiman, Alex; Voronov, Elena; Apte, Ron N. (Frontiers in Immunology, 2012)
During hypoxia, cells undergo transcriptional changes to adjust to metabolic stress, to promote cell survival and to induce pro-angiogenic factors. Hypoxia induced factors (HIFs) regulate these transcriptional alterations. Failure to restore oxygen levels results in cell death by necrosis. IL-1 alpha is one of the most important mediators of sterile inflammation following hypoxia-mediated necrosis. During hypoxia, IL-1 alpha is up-regulated and released from necrotic cells, promoting the initiation of sterile inflammation. This study examined the role of IL-1 alpha transcription in initiation of hypoxic stress and the correlation between IL-1 alpha transcription and HIF alpha factors. In an epithelial cell line cultured under hypoxic conditions, IL-1 alpha transcription was up-regulated in a process mediated and promoted by HIF alpha factors. IL-1 alpha transcription was also up-regulated in hypoxia in a fibroblast cell line, however, in these cells, HIF alpha factors inhibited the elevation of transcription. These data suggest that HIF alpha factors play a significant role in initiating sterile inflammation by controlling IL-1 alpha transcription during hypoxia in a differential manner, depending on the cell type.